Application of the Assignment Method to Improve Student Learning Outcomes in Learning English - Adieli Laoli (Universitas Muhammadiyah Enrekang, 2020)
This study aims to improve activities and learning outcomes of English by giving assignments to class X SMA Negeri 1 Gunungsitoli. This type of research is Classroom Action Researcher. The strategy of this research is to carry out action planning, observation, analysis and reflection steps. Data collection techniques to obtain data in this study include tests and direct observation. The results showed that the activity and improvement of student learning outcomes obtained an average learning outcome in the first cycle of 69,54. Cycle II obtained the average value of learning outcomes that is 89,97. The results of the study concluded that learning by using the assignment method can increase students' learning outcomes in Class X students of SMA Negeri 1 Gunungsitoli by providing reinforcement, more students to participate in learning.